Low-thermal-conductivity photo-thermal conversion composite phase change material as well as preparation method and application thereof
By using pretreated expanded perlite and silver nanoparticles in the photothermal conversion phase change material, combined with hydrothermal reaction and melt mixing technology, a low-thermal conductivity photothermal conversion composite phase change material was prepared, which solved the problems of high thermal conductivity and uneven dispersion of silver nanoparticles, and achieved efficient photothermal conversion and low thermal conductivity.
Patent Information
- Application Number
- CN202411862053.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing photothermal conversion phase change materials have a high thermal conductivity coefficient and cannot meet the requirements of low thermal conductivity. At the same time, silver nanoparticles are difficult to disperse uniformly in the material, affecting the photothermal conversion performance.
After impregnating the pretreated expanded perlite into the silver nitrate solution, a hydrothermal reaction was performed to prepare a silver/expanded perlite complex, and mixed with hydrated inorganic salts and nucleating agent, and then cooling was made to obtain a low-thermal conductivity photothermal conversion composite phase change material.
The preparation of low thermal conductivity photothermal conversion composite phase change materials is achieved, with thermal conductivity as low as 0.16W/(m·K), and the photothermal conversion efficiency is greater than 85%. At the same time, the heat storage density and photothermal conversion performance of phase change materials are ensured.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of phase change heat storage materials, and specifically relates to a low thermal conductivity photothermal conversion composite phase change material and a preparation method and application thereof. Background Art
[0002] Phase change heat storage technology uses the characteristic of materials that can absorb or release a large amount of latent heat during the phase change process to achieve heat storage. Photothermal conversion phase change materials are based on conventional phase change materials and are endowed with the ability to efficiently absorb solar radiation, while achieving solar thermal conversion and heat storage. The performance of photothermal conversion phase change materials in the solar thermal storage process is not only affected by the material's heat storage density, photothermal conversion efficiency, phase change temperature, etc., but is also closely related to the material's thermal conductivity. Among them, high thermal conductivity phase change materials are suitable for large-scale solar thermal storage, while in aspects such as building exterior wall insulation, phase change materials are required to have a low thermal conductivity coefficient.
[0003] At present, the widely studied photothermal conversion phase change materials mostly use carbon materials as light absorption enhancers, such as expanded graphite, carbon nanotubes, graphite fibers, etc. However, the thermal conductivity of the composite phase change materials formed by these carbon materials and phase change materials is usually high and cannot meet the requirements of low thermal conductivity. Expanded perlite, as a cheap and readily available building material, has a low thermal conductivity. Studies have shown that low thermal conductivity composite phase change materials can be prepared using expanded perlite as an adsorption material. However, both expanded perlite and phase change raw materials have weak absorption capacity for solar radiation. After the two form a composite phase change material, effective absorption of solar radiation cannot be achieved.
[0004] The local surface plasmon resonance effect of silver nanoparticles makes them have a strong absorption capacity for solar radiation. If the silver nanoparticles can be evenly dispersed in the phase change material, a composite phase change material with photothermal conversion ability can be obtained. However, the surface energy of silver nanoparticles is high and they are easy to agglomerate. It is difficult to obtain monodispersed silver nanoparticles by directly mixing silver nanoparticles with expanded perlite or phase change materials, which not only affects the photothermal conversion performance of the phase change material, but also has an adverse effect on the uniformity and mechanical properties of the material. Due to the large-scale agglomeration of silver nanoparticles, a higher content of silver is required to produce an ideal photothermal conversion effect. A higher content of silver will not only increase the thermal conductivity of the composite material, but also increase the material manufacturing cost. Therefore, how to evenly disperse silver nanoparticles in expanded perlite or phase change materials is the key to preparing low thermal conductivity photothermal conversion composite phase change materials. Summary of the invention
[0005] The purpose of the present invention is to provide a low thermal conductivity photothermal conversion composite phase change material and its preparation method and application, so as to overcome the shortcomings of the prior art and achieve a lower thermal conductivity while ensuring the heat storage density and photothermal conversion performance of the phase change material.
[0006] In order to achieve the above object, the technical solution of the present invention is:
[0007] In a first aspect, the present invention provides a method for preparing a low thermal conductivity photothermal conversion composite phase change material, comprising the following steps:
[0008] (1) After the pretreated expanded perlite is immersed in a silver nitrate solution, a sodium citrate solution is added to carry out a hydrothermal reaction to obtain a silver / expanded perlite composite;
[0009] (2) After the hydrated inorganic salt and the nucleating agent are mixed and melted, the silver / expanded perlite composite is added and mixed, and after cooling, a low thermal conductivity photothermal conversion composite phase change material is obtained.
[0010] In some other embodiments, in step (1), the pretreatment method of the expanded perlite is: heating the expanded perlite at 400-500° C. for 1-5 hours, and the particle size of the expanded perlite is 10-30 mesh.
[0011] In some other embodiments, in step (1), the concentration of the silver nitrate solution is 1-10 mM, the concentration of the sodium citrate solution is 0.1-0.5 M, and the molar ratio of silver nitrate to sodium citrate is 1:2-1:5.
[0012] In some other embodiments, in step (1), the immersion is performed by stirring and mixing at 75-85° C. for 10-60 min;
[0013] Or, the temperature of the hydrothermal reaction is 75-85°C and the time is 1-5h;
[0014] Alternatively, after the hydrothermal reaction is completed, the product may be filtered, rinsed and dried.
[0015] The drying is carried out in a nitrogen environment at 80-100° C. for 1-5 hours;
[0016] Preferably, in step (1), the immersion is performed by stirring and mixing at 80° C. for 30 min;
[0017] Or, the temperature of the hydrothermal reaction is 80° C. and the time is 2 h;
[0018] Alternatively, the drying is performed in a nitrogen environment at 100° C. for 3 hours.
[0019] In some other embodiments, in step (2), the hydrated inorganic salt is one of sodium acetate trihydrate, calcium chloride hexahydrate, sodium thiosulfate pentahydrate, sodium carbonate decahydrate and disodium hydrogen phosphate dodecahydrate;
[0020] The nucleating agent is one of disodium hydrogen phosphate, strontium chloride hexahydrate and sodium silicate nonahydrate;
[0021] The amount of the nucleating agent added is 1-5 wt.% of the hydrated inorganic salt.
[0022] In some other embodiments, in step (2), the mixing mass ratio of the hydrated inorganic salt to the silver / expanded perlite composite is (2-4): (3-1).
[0023] In a second aspect, the present invention provides a low thermal conductivity photothermal conversion composite phase change material obtained by the preparation method of the low thermal conductivity photothermal conversion composite phase change material described in the first aspect.
[0024] In some other embodiments, the invention comprises an expanded perlite carrier and silver nanoparticles supported on the expanded perlite carrier, wherein the silver nanoparticles have a particle size of 10-100 nm.
[0025] In a third aspect, the present invention provides applications of the low thermal conductivity photothermal conversion composite phase change material described in the second aspect in solar thermal systems, building energy conservation, electronic equipment heat dissipation, and seawater desalination.
[0026] In some other embodiments, the application is application in building energy conservation.
[0027] The low thermal conductivity photothermal conversion phase change material provided by the second aspect of the present invention is filled into a hollow acrylic plate to prepare a phase change brick with a size of 30cm×30cm×2cm. A plurality of phase change bricks are laid flat on the roof of the building. When the sun shines during the day, the phase change bricks absorb solar radiation and convert it into thermal energy. Part of the heat is transferred to the room to increase the indoor temperature, and the excess heat is stored in the phase change material in the form of latent heat. When there is no sunlight at night, the heat stored in the phase change material during the day is released into the room to maintain the indoor temperature. The phase change material absorbs solar radiation and stores heat, which plays a role in increasing the indoor temperature and reducing heating energy consumption.
[0028] Beneficial effects of the present invention:
[0029] 1) The present invention pre-treats the commercial expanded perlite by heating to remove water and impurities adsorbed by the expanded perlite, which is beneficial to the generation of uniformly dispersed silver nanoparticles.
[0030] 2) The composite phase change material provided by the present invention uses expanded perlite as an adsorption material to ensure low thermal conductivity of the composite material; silver nanoparticles are prepared in situ using a mild chemical reaction, which is conducive to the uniform dispersion of silver nanoparticles on the surface of expanded perlite, and the surface plasmon resonance effect is used to make up for the poor light absorption capacity of expanded perlite. Expanded perlite and silver nanoparticles work synergistically to achieve low thermal conductivity and high light-to-heat conversion.
[0031] 3) The present invention uses expanded perlite as an adsorption material, which is cheaper than carbon materials such as expanded graphite and graphene. The thermal conductivity of the composite phase change material is as low as 0.16W / (m·K), the solar thermal conversion efficiency is greater than 85%, the highest is 91%, and the phase change temperature is 25-60°C. The silver nanoparticles are prepared by a mild hydrothermal method, which is simple and economical. DETAILED DESCRIPTION
[0032] Unless otherwise specified, the raw materials used in the preparation of the low thermal conductivity photothermal conversion composite phase change material of the present invention, namely expanded perlite, silver nitrate, sodium citrate dihydrate, hydrated inorganic salt and nucleating agent, are all commercially available products.
[0033] Example 1
[0034] (1) Weigh 30 g of expanded perlite with a particle size of 18-30 mesh, put it into a muffle furnace, heat it to 400 degrees at a rate of 10 degrees Celsius per minute, and keep it warm for 2 hours to obtain pretreated expanded perlite.
[0035] (2) Weigh 0.34 g of silver nitrate, dissolve it in 200 g of deionized water, and heat it to 80° C. using a magnetic stirrer with a heating function. Immerse the pretreated expanded perlite obtained in step (1) in the silver nitrate solution and continue stirring for 30 minutes. Weigh 1.776 g of sodium citrate dihydrate, dissolve it in 20 g of deionized water, and slowly add it to the mixture of expanded perlite and silver nitrate, and continue stirring for 2 hours.
[0036] (3) The mixture was filtered, rinsed with deionized water three times, and heated in a nitrogen muffle furnace at 100° C. for 3 hours to remove water adsorbed by the expanded perlite, thereby obtaining silver / expanded perlite.
[0037] (4) Weigh 20 g of sodium acetate trihydrate, add 0.2 g of disodium hydrogen phosphate as a nucleating agent, mix well, and heat in a blast drying oven at 80° C. until melted. Mix well with the silver / expanded perlite obtained in step (3) by mechanical stirring, and after cooling to room temperature, obtain a low thermal conductivity photothermal conversion composite phase change material with a phase change temperature of about 58° C.
[0038] Example 2
[0039] (1) Weigh 20 g of expanded perlite with a particle size of 18-30 mesh, put it into a muffle furnace, heat it to 400 degrees at a rate of 10 degrees Celsius per minute, and keep it warm for 2 hours to obtain pretreated expanded perlite.
[0040] (2) Weigh 0.34 g of silver nitrate, dissolve it in 200 g of deionized water, and heat it to 80° C. using a magnetic stirrer with a heating function. Immerse the pretreated expanded perlite obtained in step (1) in the silver nitrate solution and continue stirring for 30 minutes. Weigh 1.176 g of sodium citrate dihydrate, dissolve it in 20 g of deionized water, and slowly add it to the mixture of expanded perlite and silver nitrate, and continue stirring for 2 hours.
[0041] (3) The mixture was filtered, rinsed with deionized water three times, and heated in a nitrogen muffle furnace at 100° C. for 3 hours to remove water adsorbed by the expanded perlite, thereby obtaining silver / expanded perlite.
[0042] (4) Weigh 80 g of sodium acetate trihydrate, add 0.8 g of disodium hydrogen phosphate as a nucleating agent, mix well, and heat in a blast drying oven at 80° C. until melted. Mix well with the silver / expanded perlite obtained in step (3) by mechanical stirring, and after cooling to room temperature, obtain a low thermal conductivity photothermal conversion composite phase change material with a phase change temperature of about 58° C.
[0043] Example 3
[0044] (1) Weigh 30 g of expanded perlite with a particle size of 18-30 mesh, put it into a muffle furnace, heat it to 400 degrees at a rate of 10 degrees Celsius per minute, and keep it warm for 2 hours to obtain pretreated expanded perlite.
[0045] (2) Weigh 0.34 g of silver nitrate, dissolve it in 200 g of deionized water, and heat it to 80° C. using a magnetic stirrer with a heating function. Immerse the pretreated expanded perlite obtained in step (1) in the silver nitrate solution and continue stirring for 30 minutes. Weigh 1.176 g of sodium citrate dihydrate, dissolve it in 20 g of deionized water, and slowly add it to the mixture of expanded perlite and silver nitrate, and continue stirring for 2 hours.
[0046] (3) The mixture was filtered, rinsed with deionized water three times, and heated in a nitrogen muffle furnace at 100° C. for 3 hours to remove water adsorbed by the expanded perlite, thereby obtaining silver / expanded perlite.
[0047] (4) Weigh 30 g of calcium chloride hexahydrate, add 0.6 g of strontium chloride hexahydrate as a nucleating agent, mix well, and heat in a 50° C. air drying oven until melted. Mix well with the silver / expanded perlite obtained in step (3) by mechanical stirring, and after cooling to room temperature, obtain a low thermal conductivity photothermal conversion composite phase change material with a phase change temperature of about 28° C.
[0048] Example 4
[0049] (1) Weigh 30 g of expanded perlite with a particle size of 18-30 mesh, put it into a muffle furnace, heat it to 400 degrees at a rate of 10 degrees Celsius per minute, and keep it warm for 2 hours to obtain pretreated expanded perlite.
[0050] (2) Weigh 0.34 g of silver nitrate, dissolve it in 200 g of deionized water, and heat it to 80° C. using a magnetic stirrer with a heating function. Immerse the pretreated expanded perlite obtained in step (1) in the silver nitrate solution and continue stirring for 30 minutes. Weigh 1.176 g of sodium citrate dihydrate, dissolve it in 20 g of deionized water, and slowly add it to the mixture of expanded perlite and silver nitrate, and continue stirring for 2 hours.
[0051] (3) The mixture was filtered, rinsed with deionized water three times, and heated in a nitrogen muffle furnace at 100° C. for 3 hours to remove water adsorbed by the expanded perlite, thereby obtaining silver / expanded perlite.
[0052] (4) Weigh 30 g of disodium hydrogen phosphate dodecahydrate, add 1.2 g of sodium silicate nonahydrate, mix well, and heat in a 50° C. air drying oven until melted. Mix well with the silver / expanded perlite obtained in step (3) by mechanical stirring, and after cooling to room temperature, obtain a low thermal conductivity photothermal conversion composite phase change material with a phase change temperature of about 35° C.
[0053] Comparative Example 1
[0054] (1) Weigh 30 g of expanded perlite with a particle size of 18-30 mesh, put it into a muffle furnace, heat it to 400 degrees at a rate of 10 degrees Celsius per minute, and keep it warm for 2 hours to obtain pretreated expanded perlite.
[0055] (2) Weigh 20 g of sodium acetate trihydrate, add 0.2 g of disodium hydrogen phosphate as a nucleating agent, mix well, and heat in a blast drying oven at 80° C. until melted. Mix well with the pretreated expanded perlite obtained in step (1) by mechanical stirring, and cool to room temperature to obtain a composite phase change material with a phase change temperature of about 58° C.
[0056] Comparative Example 2
[0057] (1) Weigh 30 g of expanded graphite with a particle size of 50 mesh, put it into a muffle furnace, heat it to 400 degrees at a rate of 10 degrees Celsius per minute, and keep it at this temperature for 2 hours.
[0058] (2) Weigh 20 g of sodium acetate trihydrate, add 0.2 g of disodium hydrogen phosphate as a nucleating agent, mix well, and heat in a blast drying oven at 80° C. until melted. Mix well with the expanded graphite obtained in step (1) by mechanical stirring, and after cooling to room temperature, obtain a composite phase change material with a phase change temperature of about 58° C.
[0059] Comparative Example 3
[0060] The difference from Example 1 is that step (1) is omitted, that is, the expanded perlite is not pretreated, and the other preparation steps are exactly the same as those in Example 1.
[0061] Comparative Example 4
[0062] The difference from Example 1 is that 2 grams of 50 nm silver particles are directly mechanically mixed with the pretreated expanded perlite, and the other preparation steps are exactly the same as those in Example 1.
[0063] The performance tests of the embodiments and comparative examples are shown in Table 1.
[0064] Table 1 Material test results
[0065] Case Phase transition temperature℃ Latent heat of phase change J / g Thermal conductivity W / (m·K) Photothermal conversion efficiency % Example 1 58.3 98.4 0.192 89 Example 2 58.8 201 0.263 85 Example 3 28.4 88.2 0.200 91 Example 4 35.4 108 0.221 85 Comparative Example 1 57.8 100.5 0.197 15 Comparative Example 2 57.5 104.4 3.62 88 Comparative Example 3 57.5 101.2 0.203 76 Comparative Example 4 57.5 90.3 0.355 56
[0066] As can be seen from Table 1, the maximum thermal conductivity of the composite phase change materials of Examples 1-4 is 0.263W / (m·K), and the photothermal conversion efficiency is greater than 85%, indicating that the photothermal conversion composite phase change material with low thermal conductivity has been successfully prepared. Among them, the low thermal conductivity is attributed to the thermal insulation of the expanded perlite itself (the thermal conductivity is about 0.1W / (m·K)). When the expanded perlite is compounded with the inorganic hydrated salt, the thermal conductivity does not increase significantly. In Example 2, the mass ratio of the hydrated inorganic salt to silver / expanded perlite is 4:1, which is the largest ratio and therefore the phase change latent heat is the largest. The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not load silver nanoparticles on the surface of the expanded perlite, so the photothermal conversion efficiency of the composite phase change material is significantly lower than that of Example 1.
[0067] Comparative Example 2 uses expanded graphite to replace the expanded perlite in Comparative Example 1. Although Comparative Example 2 presents a light-to-heat conversion efficiency of 88%, the thermal conductivity is as high as 3.62W / (m·K), which cannot meet the requirements of low thermal conductivity for building exterior walls. In Comparative Example 3, the expanded perlite was not pretreated, and the impurities in the expanded perlite may affect the generation of silver nanoparticles, so its light-to-heat conversion efficiency is low.
[0068] Comparative Example 4 adopts a mechanical mixing method. Since the particle size of the expanded perlite is large, and the particle size of the silver nanoparticles is small and very easy to agglomerate, the dispersion effect of the silver nanoparticles prepared by the mechanical mixing method is poorer than that of the in-situ growth in Example 1, resulting in a lower light-to-heat conversion efficiency. In addition, compared with Example 1, the silver particles in this comparative example account for 3.8% of the mass of the composite phase change material, while the mass of silver in Example 1 is almost negligible. This not only increases the thermal conductivity of the composite material, but also reduces the phase change latent heat of the composite phase change material.
[0069] In addition, the raw materials of the present invention, expanded perlite and phase change material, are both cheap and readily available, the preparation process is simple, the reaction conditions are mild, the cost is low, and they are suitable for large-scale production and application.
[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a low thermal conductivity photothermal conversion composite phase change material, characterized in that: The following steps are involved: (1) After the pretreated expanded perlite is immersed in a silver nitrate solution, a sodium citrate solution is added to carry out a hydrothermal reaction to obtain a silver / expanded perlite composite; (2) After the hydrated inorganic salt and the nucleating agent are mixed and melted, the silver / expanded perlite composite is added and mixed, and after cooling, a low thermal conductivity photothermal conversion composite phase change material is obtained.
2. The method for preparing a low thermal conductivity light-to-heat conversion composite phase change material according to claim 1, characterized in that: In step (1), the pretreatment method of the expanded perlite is: heating the expanded perlite at 400-500° C. for 1-5 hours, and the particle size of the expanded perlite is 10-30 meshes.
3. The method for preparing a low thermal conductivity light-to-heat conversion composite phase change material according to claim 1, characterized in that: In step (1), the concentration of the silver nitrate solution is 1-10 mM, the concentration of the sodium citrate solution is 0.1-0.5 M, and the molar ratio of silver nitrate to sodium citrate is 1:2-1:
5.
4. The method for preparing a low thermal conductivity light-to-heat conversion composite phase change material according to claim 1, characterized in that: In step (1), the immersion is carried out by stirring and mixing at 75-85° C. for 10-60 minutes; Or, the temperature of the hydrothermal reaction is 75-85°C and the time is 1-5h; Alternatively, after the hydrothermal reaction is completed, the product may be filtered, rinsed and dried. The drying is carried out in a nitrogen environment at 80-100° C. for 1-5 hours; Preferably, in step (1), the immersion is performed by stirring and mixing at 80° C. for 30 min; Or, the temperature of the hydrothermal reaction is 80° C. and the time is 2 h; Alternatively, the drying is performed in a nitrogen environment at 100° C. for 3 hours.
5. The method for preparing a low thermal conductivity light-to-heat conversion composite phase change material according to claim 1, characterized in that: In step (2), the hydrated inorganic salt is one of sodium acetate trihydrate, calcium chloride hexahydrate, sodium thiosulfate pentahydrate, sodium carbonate decahydrate and disodium hydrogen phosphate dodecahydrate; The nucleating agent is one of disodium hydrogen phosphate, strontium chloride hexahydrate and sodium silicate nonahydrate; The addition amount of the nucleating agent is 1-5 wt.% of the hydrated inorganic salt.
6. The method for preparing a low thermal conductivity light-to-heat conversion composite phase change material according to claim 1, characterized in that: In step (2), the mixing mass ratio of the hydrated inorganic salt to the silver / expanded perlite composite is (2-4): (3-1).
7. A low thermal conductivity photothermal conversion composite phase change material obtained by the preparation method of the low thermal conductivity photothermal conversion composite phase change material according to any one of claims 1 to 6.
8. The low thermal conductivity light-to-heat conversion composite phase change material according to claim 7, characterized in that: The invention comprises an expanded pearlite carrier and silver nanoparticles loaded on the expanded pearlite carrier, wherein the particle size of the silver nanoparticles is 10-100nm.
9. An application of the low thermal conductivity photothermal conversion composite phase change material according to claim 7 or 8 in solar thermal systems, building energy saving, electronic equipment heat dissipation and seawater desalination.
10. The use according to claim 9, characterized in that: The application is application in building energy conservation.
Citation Information
Patent Citations
Composite phase change heat storage material and preparation method thereof
CN103194179A
High thermal conductivity light-heat converting compound phase-changeable heat storage material for solar water heater and preparation method thereof
CN109181649A
High-temperature composite phase change heat storage material and preparation method thereof
CN115074090A
Carbon-based expanded perlite phase change energy storage material as well as preparation method and application thereof
CN116924767A
Phase-change heat-preservation and heat-insulation composite material and preparation method thereof
CN118703177A